A magnetic ZrO2 based solid-phase extraction strategy for selective enrichment and profiling of glycosylated compounds in rice. Issue 34 (11th August 2016) - Jiang, Meng-Ying; Huang, Yun-Qing; Chu, Jie-Mei; Zhu, Quan-Fei; Ding, Jun; Yuan, Bi-Feng; Feng, Yu-Qi
Abstract : A magnetic ZrO2 -based solid-phase extraction strategy combined with LC-HRMS for selective enrichment and profiling of glycosylated small molecules in rice. Abstract : Glycosylation of small molecules is one of the most widespread modifications which involve various physiological functions in plants. However, the determination of glycosylated small molecules is still challenging due to their low abundance and serious matrix interference in biological samples. Here, we developed a strategy for comprehensive profiling of glycosylated small molecules in rice using magnetic zirconium dioxide (ZrO2 )-based solid-phase extraction combined with liquid chromatography-high resolution mass spectrometry (MSPE-LC-HRMS) analysis. Optimization of several experimental parameters was carried out on standard glycosylated compounds. Our results showed that magnetic ZrO2 exhibited high specificity toward 1, 2- cis -diol and 1, 3- cis -diol glycosyl-containing compounds. With the developed MSPE-LC-HRMS strategy, we successfully identified 27 glycosylated small molecules in rice samples, and a significant content change was observed in 6 glycosylated small molecules between cadmium (Cd)-free and Cd-stressed rice.